2018
DOI: 10.1371/journal.pone.0191805
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and metformin inhibit cell growth in hepatitis C virus infected cells via mTOR increasing PTEN and autophagy

Abstract: Hepatitis C virus (HCV) infection has been related to increased risk of development of hepatocellular carcinoma (HCC) while metformin (M) and statins treatment seemed to protect against HCC development. In this work, we aim to identify the mechanisms by which metformin and simvastatin (S) could protect from liver cancer. Huh7.5 cells were infected with HCV particles and treated with M+S. Human primary hepatocytes were treated with M+S. Treatment with both drugs inhibited Huh7.5 cell growth and HCV infection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 46 publications
4
33
0
Order By: Relevance
“…PTEN plays complex roles in multiple cellular processes including proliferation, survival, apoptosis, cell cycle regulation, adhesion, and migration [21,44]. In our study, PTEN expression was reduced upon MTFN treatment, in line with previous studies [45,46], but this reduction was compensated following MTFN/CURC co-treatment. Cell death induction by co-treatment suggests that the co-presence of MTFN and CURC may strengthen the anti-tumor activities of PTEN via engaging several pathways and factors including miR-21 and Akt/PI3K [47].…”
Section: Discussionsupporting
confidence: 91%
“…PTEN plays complex roles in multiple cellular processes including proliferation, survival, apoptosis, cell cycle regulation, adhesion, and migration [21,44]. In our study, PTEN expression was reduced upon MTFN treatment, in line with previous studies [45,46], but this reduction was compensated following MTFN/CURC co-treatment. Cell death induction by co-treatment suggests that the co-presence of MTFN and CURC may strengthen the anti-tumor activities of PTEN via engaging several pathways and factors including miR-21 and Akt/PI3K [47].…”
Section: Discussionsupporting
confidence: 91%
“…In other viral settings, orlistat and metformin were shown to inhibit replication of several flaviviruses [ 109 , 110 , 111 , 112 ], as well as hepatitis B virus and HCV [ 113 , 114 , 115 , 116 , 117 ], coxsackievirus B3 and varicella-zoster virus [ 118 , 119 ]. For these viruses, orlistat was shown to inhibit lipid-vesicle restructuring, viral genome replication, virion protein palmitoylation [ 109 , 110 , 111 , 118 ] and virus entry [ 113 , 114 ].…”
Section: Potential Use Of Orlistat and Metformin In Controlling Samentioning
confidence: 99%
“…For these viruses, orlistat was shown to inhibit lipid-vesicle restructuring, viral genome replication, virion protein palmitoylation [ 109 , 110 , 111 , 118 ] and virus entry [ 113 , 114 ]. Metformin was shown to decrease lipid (palmitate) synthesis [ 119 ], viral RNA transcription and protein synthesis [ 115 , 116 ], as well as virus-dependent glycolysis, while increasing IFN production and blocking inflammatory cytokines [ 112 , 117 ]. From these observed antiviral mechanisms, orlistat and metformin are expected to decrease FASN and activate AMPK, respectively, for a predicted inhibition of viral replication organelle formation, and to block spike, membrane and envelope palmitoylation and subsequent virus assembly.…”
Section: Potential Use Of Orlistat and Metformin In Controlling Samentioning
confidence: 99%
“…Wang et al 24 demonstrated the effects of MET in cancer, detailing that this drug inhibits abnormal cell proliferation by modifying the tumor microenvironment, which causes decreased angiogenesis, as well as by altering the tumor-associated macrophage phenotype that subsidises tumor development. 24 In hepatocellular carcinoma, Del Campo et al 25 and Choi and Roberts 26 corroborated findings reaffirming the direct action of MET in AMPK induction, mTOR inhibition, cell cycle suppression and the consequent proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 78%